Zeolite molecular sieve catalyst loaded with cobalt single atoms as well as preparation method and application of zeolite molecular sieve catalyst
The zeolite molecular sieve catalyst loaded with cobalt single atoms activated monosulfate, transforming the micro reaction environment, solving the problems of high energy consumption and pollution in PVC microplastic treatment, and achieving efficient microplastic depolymerization and resource utilization.
Patent Information
- Application Number
- CN202411251516.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-07
- Publication Date
- 2024-12-13
AI Technical Summary
The prior art has problems of high energy consumption, pollution and degradation efficiency when dealing with polyvinyl chloride (PVC) microplastics, making it difficult to achieve efficient and environmentally friendly microplastic depolymerization technology.
Using a zeolite molecular sieve catalyst with cobalt-loaded single atoms, the Co monoatoms are uniformly fixed in the octane zeolite molecular sieve, the persulfate is activated, the micro reaction environment is modified, and the efficiency of heterogeneous Fenton oxidation reaction is improved, and PVC microplastics is realized. efficient degradation.
Depolymerization of 17 wt% PVC microplastic particles was achieved within 48 hours at room temperature, which significantly reduced the particle size, improved the stability and reuse of the catalyst, and provided low-cost and high-efficiency PVC chemical bond fracture and resource utilization. Theoretical basis.
Smart Images

Figure CN119114142A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyvinyl chloride (PVC) processing, and in particular relates to a zeolite molecular sieve catalyst loaded with cobalt (Co) single atoms, and a preparation method and application thereof. Background Art
[0002] Plastics are widely used in human production and life due to their advantages such as light weight, corrosion resistance and stable chemical properties. The global annual production of plastics is about 400 million tons, accounting for 6% of global oil consumption. The greenhouse gas emissions caused by plastics are about 5%, and it is expected to reach 15% in 2050. Nearly 80% of the plastics currently produced and used will eventually become plastic waste and be buried or accumulated in the environment. The treatment and conversion methods of plastics include traditional physical methods such as landfill, incineration, and mechanical recycling, as well as newer catalytic technologies such as thermal catalysis, electrocatalysis, and photocatalysis. Common waste plastic treatment methods, including pyrolysis, landfill, hydrogenation and biomass conversion, are energy-intensive and will produce a large amount of microplastics, causing high pollution, hindering the sustainable closed-loop utilization of plastics. In recent years, the problem of microplastic pollution in oceans, rivers, soil, air and drinking water has attracted more and more attention. Microplastic pollution in water refers to plastic fibers with a diameter of less than 5mm in the water, including tiny plastic particles in the form of microbeads, microfibers and films. This pollution originates from the decomposition and release of plastic products during production, use and disposal. Microplastic particles are easily carried into the water by water flow, accumulating on the surface of the water, in the bottom mud and in aquatic organisms, affecting the growth, development, reproduction and food chain structure of aquatic organisms, and destroying the balance and stability of aquatic ecosystems. Microplastic pollution in water poses a serious threat to aquatic ecosystems and human health, and has become one of the serious challenges to global environmental issues.
[0003] At present, plastic materials such as polyvinyl chloride (PVC), polypropylene (PP), polyethylene (PE), polystyrene (PS), polyethylene terephthalate (PET) and polylactic acid (PLA) are the most widely distributed categories of microplastic pollution in water. Among them, polyvinyl chloride (PVC) is a common representative plastic material obtained by polymerization of vinyl chloride monomer (Vinyl Chloride). Its chemical structure contains chlorine atoms, which makes PVC have good weather resistance and chemical stability. Polyvinyl chloride is widely used in construction, electrical, medical and packaging fields, bringing convenience and safety to modern industry and life. However, PVC may release harmful substances (such as dioxins and hydrochloric acid) during production and use, and its degradation rate is slow, resulting in its long-term accumulation in the natural environment, bringing great pressure and harm to the environment and ecosystem. At present, plastic degradation requires acidification, alkalization or high temperature and high pressure treatment, and the acidification and alkalization methods of plastic treatment face the problems of material compatibility and the possible impact of degradation products on the environment. In addition, although high temperature and high pressure plastic treatment technology is helpful for converting waste plastics, it has significant disadvantages, including high energy consumption, strict equipment requirements, secondary pollution, technical complexity, product selectivity and distribution problems, unclear microscopic mechanism and catalyst tolerance. Therefore, finding an efficient, selective and environmentally friendly PVC microplastic depolymerization technology is still a difficult problem.
[0004] The Fenton-like oxidation process of persulfates (peroxydisulfate (PDS) and peroxymonosulfate (PMS)) has received extensive attention in water treatment. The activation of persulfates firstly leads to electron transfer through the adsorption of persulfate on metal centers and then produces reactive species (ROS), including non-free radicals (i.e. 1 O 2 , high-valent metals and metal-PMS complexes) and free radicals (i.e., O 2 ·- , OH and SO 4 ·-). Recent studies have shown that the chemical activity and stability of metal-based catalysts are highly dependent on the electronic and geometric structures of the metal sites. In this case, short-lived active substances and target pollutants are encapsulated within the nanoscale diffusion length, which helps to achieve the transformation of the microscopic reaction environment at the nanoscale to improve the effective utilization efficiency of active substances in heterogeneous Fenton-like oxidation reactions, which can serve as a powerful basis for designing new functional catalysts. Molecular sieves are crystalline materials with highly ordered pore structures, which provide an ideal microscopic environment for nano-confined environments. Commonly used molecular sieve catalysts include zeolites, ZSM-5 and Beta, which have different pore sizes and pore structures. The rate and selectivity of the depolymerization reaction can be improved by the pore structure of molecular sieves. The confinement effect of molecular sieves is mainly reflected in its regular pore structure and pore size range, which makes the molecular sieve surface have specific local charge density and active sites, such as: electronic state, electron transfer, mass transfer, phase behavior and reaction rate will undergo fundamental changes, thereby changing the catalytic performance of the system. The pore size significantly affects the van der Waals force between the catalyst and the pollutant, the degree of enrichment, the residence time, the distance of ROS transmission to the pollutant, and the reaction space between the free radicals and the pollutant. In addition, molecular sieves can prevent non-specific interactions between activated persulfate molecules through spatial arrangement and restriction, which helps to improve the stereoselectivity of the reaction and the purity of the product. Therefore, designing a suitable molecular sieve catalyst and carrying out the catalytic reaction under appropriate reaction conditions can achieve efficient and selective degradation of PVC microplastics into low molecular weight compounds, thereby achieving the removal and resource utilization of microplastics, which is of great significance. Summary of the invention
[0005] In view of the deficiencies of the prior art, the object of the present invention is to provide a zeolite molecular sieve catalyst loaded with single cobalt atoms.
[0006] Another object of the present invention is to provide a method for preparing the above-mentioned zeolite molecular sieve catalyst loaded with cobalt single atoms.
[0007] Another object of the present invention is to provide an application of a zeolite molecular sieve catalyst loaded with single cobalt atoms in the degradation of PVC microplastics, so as to solve the problems existing in the above-mentioned prior art and achieve rapid and efficient conversion of PVC.
[0008] The purpose of the present invention is achieved through the following technical solutions.
[0009] The invention discloses a zeolite molecular sieve catalyst loaded with cobalt single atom, wherein the Co content in the zeolite molecular sieve catalyst loaded with cobalt single atom is 1-3wt%.
[0010] The method for preparing the above-mentioned zeolite molecular sieve catalyst loaded with cobalt single atoms comprises the following steps:
[0011] 1) Dispersing a Co source uniformly in a solvent, adding an ethylene polyamine organic amine and mixing until uniform, then adding an Al source, an alkali metal source and an inorganic silicon source and mixing until uniform to obtain a mixture, reacting the mixture at 100-150° C. for 1-2 days to obtain a reactant gel, wherein, by molar mass, the ratio of Co in the Co source, Al in the Al source and alkali metal in the alkali metal source is (9-27):(90-95):(935-940);
[0012] In the step 1), the ratio of the amount of Co in the Co source, the volume of the solvent, the volume of the ethylene polyamine organic amine and the volume of the inorganic silicon source is (51-154): (60-100): 1: (10-13), the unit of the amount of the substance is mmol, and the unit of the volume is mL.
[0013] In step 1), the Co source is Co(NO 3 ) 2 6H 2 O, Al source is NaAlO 2 , the alkali metal source is NaOH, and the inorganic silicon source is colloidal silica.
[0014] In the step 1), the solvent is deionized water.
[0015] In the step 1), the ethylene polyamine organic amine is diethylene triamine (DETA).
[0016] In the step 1), the mixing to uniformity is achieved by stirring at room temperature, and the stirring time is 1 to 4 hours.
[0017] 2) washing the reactant gel to neutrality, drying, and calcining at 500-600° C. for 5-7 h to obtain a calcined sample;
[0018] In the step 2), the calcination atmosphere is air.
[0019] In the above technical solution, the air flow rate is 9-11 mL min -1 .
[0020] In step 2), the rate of heating to 500-600°C is 1-3°C·min -1 .
[0021] 3) The calcined sample is subjected to multiple ion exchanges, dried after the ion exchange, and calcined at 60-90° C. for 5-7 h to obtain a zeolite molecular sieve catalyst (octahedral zeolite molecular sieve catalyst) loaded with cobalt single atoms, wherein each ion exchange operation comprises: immersing the calcined sample in 50-80° C. NaNO 3Place in aqueous solution for 10 to 15 hours, remove and wash until neutral.
[0022] In step 3), the NaNO 3 The concentration of the aqueous solution is 0.8~1.1M.
[0023] In the step 3), the ion exchange is performed 2 to 4 times.
[0024] In step 2) and step 3), the drying temperature is 90-100° C. and the drying time is 10-12 hours.
[0025] In step 2) and step 3), deionized water is used for washing.
[0026] The application of the above-mentioned zeolite molecular sieve catalyst loaded with single cobalt atoms in the degradation of PVC microplastics.
[0027] In the above technical scheme, the zeolite molecular sieve catalyst loaded with single cobalt atoms achieved the depolymerization of 17 wt% of PVC microplastic particles within 48 hours at room temperature for PVC that was not acidified, alkalized or treated with high temperature and high pressure.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The present invention efficiently activates peroxymonosulfate (PMS) by uniformly fixing Co single atoms in faujasite zeolite molecular sieves, which helps to transform the microscopic reaction environment at the nanoscale, thereby improving the effective utilization efficiency of active substances in heterogeneous Fenton-like oxidation reactions, and further degrading and transforming PVC microplastic particles in water.
[0030] (2) Within 48 hours at room temperature, 17 wt% of PVC microplastic particles in the system were depolymerized, indicating that the cobalt-loaded zeolite molecular sieve catalyst has the ability to efficiently degrade PVC that has not been acidified, alkalized, or treated with high temperature and high pressure. After 48 hours of treatment, the particle size of PVC microplastic particles was significantly reduced, and the distribution of particles in the low particle size range increased, indicating that the catalyst promoted the rapid depolymerization of microplastics.
[0031] (3) Laser infrared imaging (LDIR) and Raman spectroscopy (Raman) proved that the functional groups on the long chain of PVC during the degradation process -CH 2 The strong correlation with CC fragmentation and the order of depolymerization of some functional groups.
[0032] (4) The present invention shows through theoretical calculation and experiment that the PMS adsorption capacity and electron transfer capacity of Co single atom sites are improved, thereby promoting the activation of PMS into 1 O 2 , OH and SO 4·- .
[0033] (5) Co prepared in Example 1 of the present invention 0.2 After multiple cycles of use, the chemical structure and performance of the @Fau catalyst remained stable through XRD testing. After at least 4 cycles, a mass loss rate of 17% could still be achieved at 48 hours of depolymerization, showing good stability and reusability. (6) The present invention proposes a PVC depolymerization process based on the activation of persulfate by the molecular sieve confinement effect, which can recycle waste PVC at low cost and high efficiency, reveal the intrinsic connection between the breakage of PVC chemical bonds and free radicals, and provide a theoretical basis for the efficient degradation and resource utilization of microplastics in water. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The XRD patterns of the cobalt single atom loaded zeolite molecular sieve catalysts prepared in Examples 1 to 3;
[0035] Figure 2 (a) the Fau catalyst prepared in Example 4 and the Co catalyst prepared in Example 1 0.2 Nitrogen adsorption-desorption isotherms of @Fau catalyst; (b) Fau catalyst prepared in Example 4 and Co prepared in Example 1 0.2 @Fau pore size distribution curve of the catalyst; (c) Co prepared in Example 1 0.2 @Fau catalyst in-situ ultraviolet-visible diffuse reflectance spectrum (UV-vis-NIR) at variable temperature;
[0036] Figure 3 (a) is the Co prepared in Example 1 0.2 HRTEM images of the Fau catalyst prepared in Example 4, (b) HRTEM images of the Fau catalyst prepared in Example 4, and (c) HRTEM images of the Co 0.2 HRTEM image of @Fau catalyst, (d) is the Co prepared in Example 1 0.2 @Fau catalyst, (e) is the HAADF-STEM image of the Fau catalyst prepared in Example 4, (f) is the HAADF-STEM image of the Co 0.2 HAADF-STEM image of @Fau catalyst;
[0037] Figure 4 The PVC microplastic particles in the undepolymerized PVC solution and the Co prepared in Example 1 0.2@Fau laser infrared imaging, AFM and SEM images of PVC microplastic particles depolymerized by catalyst, where (a) is a laser infrared imaging image of PVC microplastic particles in undepolymerized PVC solution, (b) is an AFM image of PVC microplastic particles in undepolymerized PVC solution, (c) is an SEM image of PVC microplastic particles in undepolymerized PVC solution, (d) is a laser infrared imaging image of PVC microplastic particles after depolymerization, (e) is an AFM image of PVC microplastic particles after depolymerization, and (f) is an SEM image of PVC microplastic particles after depolymerization;
[0038] Figure 5 (a) is the Co prepared in Example 1 0.2 @Fau catalyst depolymerization PVC microplastic particle size distribution, Figure 5 (b) is Figure 5 Normal distribution curve of particle size of PVC microplastic particles in (a);
[0039] Figure 6 The Co prepared in Example 1 0.2 @FauChart of mass loss rate of PVC microplastic particles depolymerized with catalyst and without catalyst added as a function of depolymerization time;
[0040] Figure 7 The Co prepared in Example 1 0.2 @Fau UV-vis spectra of catalyst depolymerization of PVC microplastic particles at different times;
[0041] Figure 8 (a) is the Co prepared in Example 1 0.2 @Fau Raman test of catalyst depolymerization of PVC microplastic particles at different times, Figure 8 (b) is the Co prepared in Example 1 0.2 @NMR spectra of Fau catalyst depolymerization of PVC microplastic particles at different times;
[0042] Fig. 9 (a) is the Co prepared in Example 1 0.2 Laser infrared image of the depolymerization of PVC microplastic particles by @Fau catalyst for 12 hours, (b) is the Co prepared in Example 1 0.2 Laser infrared image of @Fau catalyst depolymerizing PVC microplastic particles for 48 hours, (c) Fig. 9 Laser infrared imaging of PVC microplastic particles in (a), (d) Fig. 9 Laser infrared imaging of PVC microplastic particles in (b);
[0043] Fig.10 The Co prepared in Example 1 0.2The free radical signal spectra of different active oxygen species generated during the depolymerization of PVC by the Fau catalyst and the Fau catalyst prepared in Example 4, where (a) is 1 O 2 Free radical signal spectrum, (b) OH / SO 4 。- Electron free radical signal spectrum;
[0044] Fig.11 The Co prepared in Example 1 0.2 @Pyrolysis-gas chromatography-mass spectrometry (GC-MS) of PVC microplastic particles depolymerized by Fau catalyst at different times;
[0045] Fig.12 The Co prepared in Example 1 0.2 @Analysis of products after depolymerization of PVC microplastic particles by Fau catalyst at different times (based on GC / MS test results);
[0046] Fig.13 This is a graph showing the mass loss rate of the cobalt single atom-loaded zeolite molecular sieve catalyst prepared in Examples 2 to 3 versus depolymerization time. DETAILED DESCRIPTION
[0047] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments.
[0048] In the following examples, the Co source is cobalt nitrate hexahydrate (Co(NO 3 ) 2 6H 2 O), the Al source is sodium aluminate (NaAlO 2 ), the alkali metal source was sodium hydroxide (NaOH), the inorganic silicon source was colloidal silicon dioxide, and the ethylene polyamine organic amine was diethylenetriamine (DETA), all of which were analytically pure.
[0049] Examples 1 to 3
[0050] A method for preparing a zeolite molecular sieve catalyst loaded with a single cobalt atom comprises the following steps:
[0051] 1) Dispersing a cobalt (Co) source uniformly in a solvent, adding an ethylene polyamine organic amine dropwise, stirring at room temperature for 1 hour to mix uniformly, then adding an Al source, an alkali metal source and an inorganic silicon source, stirring at room temperature for 4 hours to mix uniformly to obtain a mixture, placing the mixture in an autoclave and reacting at 120° C. for 2 days to obtain a reactant gel, wherein, in terms of molar fractions, the ratio of Co in the Co source, Al in the Al source and the alkali metal in the alkali metal source is W, the ratio of the molar fraction of Co in the Co source, the volume fraction of the solvent, the volume fraction of the ethylene polyamine organic amine and the volume fraction of the inorganic silicon source is N, the unit of the molar fraction is mmol, the unit of the volume fraction is mL, and the solvent is deionized water;
[0052] 2) Wash the reactant gel to neutrality (pH ~ 7), dry it at 100 ° C for 12 h, and place it in a dry air atmosphere (the air flow rate is 10 mL min -1 ), at 2℃·min -1 The heating rate was increased to 550°C and calcined at 550°C for 6 h to obtain a calcined sample;
[0053] 3) In order to eliminate the influence of Co ions on the exchange sites, the calcined sample was subjected to three ion exchanges. After the ion exchange, it was dried at 100 °C for 12 h and calcined at 70 °C for 6 h to obtain a zeolite molecular sieve catalyst loaded with cobalt single atoms. The operation of each ion exchange included: soaking the calcined sample in 70 °C NaNO 3 Aqueous solution (NaNO 3 The solution was placed in the aqueous solution (with a concentration of 1 M) for 12 h, taken out, and washed with deionized water until neutral.
[0054] The element content of the obtained cobalt single atom-loaded zeolite molecular sieve catalyst was measured by ICP-MS (X7 series, Thermo Electron Corporation), and the Co element content accounted for x wt %.
[0055] The W, N, x wt % and abbreviations of the cobalt single atom-loaded zeolite molecular sieve catalysts prepared in Examples 1 to 3 are shown in Table 1.
[0056] Table 1
[0057]
[0058]
[0059] Example 4
[0060] A faujasite zeolite molecular sieve (referred to as Fau catalyst), the preparation method of which is basically the same as the preparation method of the above-mentioned embodiment 1, the only difference being that Co(NO 3 )2 6H 2 O.
[0061] Figure 1 The Co prepared in Example 1 0.2 @Fau catalyst, Co prepared in Example 2 0.1 @Fau catalyst and Co prepared in Example 3 0.3 The XRD pattern of the catalyst was measured by using Cu Kα radiation (λ = 0.15418 nm) on a Rigaku D / Max 2200PC X-ray diffractometer. 0.2 @Fau catalyst, Co prepared in Example 2 0.1 @Fau catalyst and Co prepared in Example 3 0.3 X-ray diffraction (XRD) of @Fau catalyst. The X-ray diffraction pattern confirmed the typical FAU topological structure in the pure phase. The tested zeolite molecular sieve catalysts loaded with cobalt single atoms all showed similar diffraction patterns, and the structure did not change significantly after adding different concentrations of Co ions.
[0062] The Co prepared in Example 1 was further characterized by combining BET spectra and in-situ UV-visible diffuse reflectance spectroscopy. 0.2 @Fau The chemical structure of the catalyst and the structural transformation during the synthesis process, such as Figure 2 shown. Figure 2 The Fau catalyst prepared in Example 4 and the Co catalyst prepared in Example 1 0.2 (a) Nitrogen adsorption-desorption isotherms and (b) corresponding pore size distribution curves of @Fau catalyst, N 2 The adsorption isotherm shows that Co 0.2 @Fau The catalyst has a uniform microporous structure. Figure 2 (c) is the Co prepared in Example 1 0.2 @Fau catalyst temperature in-situ ultraviolet visible diffuse reflectance spectrum (UV-vis-NIR), Co prepared in Example 1 0.2 The in-situ UV-visible-near infrared spectra of @Fau catalyst were collected on a PerkinElmer Lambda 750UV / VIS / NIR spectrometer. The temperature was set in the range of 273-823K during the test to simulate the temperature change of the zeolite molecular sieve catalyst loaded with cobalt single atoms during the calcination process. Figure 2 (c) shows similar dd transition bands at different temperatures, indicating that the Co prepared in Example 1 0.2The @Fau catalyst is structurally stable at high temperatures. The peak at 481nm shows a shift to higher wavenumbers during the heating process, and shows reversible dehydration during the cooling process. The three prominent peak wavelengths are 659nm, 586nm, and 529nm, corresponding to 4 A 2 → 4 T 2 , 4 A 2 → 4 T 1 ( 4 F) and 4 A 2 → 4 T 1 (4P) transition, indicating that Co in Co 0.2 @Fau catalyst forms a monomeric tetrahedral Co. Based on these observations, it can be expected that under hydration, the square planar tetracoordinated nickel (D4h) will transform into a distorted square planar symmetrical tetracoordinated nickel. This distorted spatial configuration breaks the D4h symmetry of the Co-O4 active center and regulates the atomic environment of the second coordination shell of the Co center, which is beneficial to improve the Co prepared in Example 1. 0.2 @Fau The activity of the catalyst.
[0063] Figure 3 (a) is the Co prepared in Example 1 0.2 HRTEM image of @Fau catalyst (resolution: 500nm), Figure 3 (d) is the Co prepared in Example 1 0.2 HAADF-STEM image of @Fau catalyst (resolution: 10nm), Figure 3 (b) is a HRTEM image of the Fau catalyst prepared in Example 4 (resolution: 50 nm). Figure 3 (e) is a HAADF-STEM image of the Fau catalyst prepared in Example 4 (resolution: 10 nm). Figure 3 (c) is the Co prepared in Example 1 0.2 HRTEM image of @Fau catalyst (resolution: 100nm), Figure 3 (f) is the Co prepared in Example 1 0.2 HAADF-STEM image of @Fau catalyst (resolution: 5nm). Figure 3 As shown, a clear pore structure is displayed before and after doping with Co atoms.
[0064] Experiment on depolymerization of PVC microplastic particles by catalyst: 500 mg PVC microplastic particles and 60 mg permonosulfate (PMS) were added to 100 ml deionized water and stirred to obtain an undepolymerized PVC solution. 10 mg of catalyst was added to the above PVC solution (the catalyst was one of the zeolite molecular sieve catalysts loaded with cobalt single atoms prepared in Examples 1 to 3) and stirred at room temperature (stirring time was 12 h, 24 h, 36 h or 48 h) to obtain a depolymerized PVC solution, wherein 60 mg PMS was added every 6 h.
[0065] Figure 4 The PVC microplastic particles in the undepolymerized PVC solution in the "catalyst depolymerization experiment on PVC microplastic particles" and the Co prepared in Example 1 0.2 @Fau catalyst was used as the "catalyst" in the "catalyst depolymerization experiment of PVC microplastic particles" to depolymerize (stirring time was 48h) PVC microplastic particles after laser infrared imaging, AFM images and SEM images. The undepolymerized PVC microplastic particles and the Co prepared in Example 1 were imaged using the Agilent 8700LDIR system infrared imaging. 0.2 @Fau catalyst depolymerized PVC microplastic particles for testing, Figure 4 (a) is a laser infrared imaging image of PVC microplastic particles in undepolymerized PVC solution. Figure 4 (d) is the laser infrared imaging image of the depolymerized PVC microplastic particles, as shown in Figure 4 (a) and Figure 4 As shown in (d), the infrared spectrum imaging of PVC microplastic particles in the undepolymerized PVC solution presents an irregular quadrilateral, while after 48h of Co 0.2 @FauAfter the catalyst is depolymerized, its edges show obvious aging etching, and the overall particle size of the particles becomes smaller. Atomic force microscopy (AFM) is used to provide higher resolution and smaller particle size changes in the morphology of microplastic particles. Figure 4 (b) is an AFM image of PVC microplastic particles in undepolymerized PVC solution. Figure 4 (e) is the AFM image of the depolymerized PVC microplastic particles. Figure 4 (b) and Figure 4 As shown in (e), there are PVC microplastic particles of different sizes (maximum particle size is 350nm) in the undepolymerized PVC solution, while after 48h depolymerization, Co 0.2 @Fau catalyst depolymerization of PVC microplastic particles is mostly depolymerized, leaving only larger PVC microplastic particles (maximum particle size of 50nm) undepolymerized. The particle size of the undepolymerized PVC microplastic particles is significantly reduced and the particle edges are smoother. The longer the time, the PVC microplastic particles continue to be Co 0.2@Fau catalyst depolymerization. Scanning electron microscopy (SEM, Hitachi SU8010) was used to observe the PVC microplastic particles in the undepolymerized PVC solution and the PVC microplastic particles in the Co 0.2 @Fau catalyst depolymerized PVC microplastic particles for 48 hours for testing, Figure 4 (c) is the SEM image of PVC microplastic particles in the undepolymerized PVC solution. Figure 4 (f) is the SEM image of PVC microplastic particles after depolymerization for 48 hours. Figure 4 (c) and Figure 4 As shown in (f), compared with the PVC microplastic particles after 48 hours of depolymerization, after 48 hours of depolymerization, Co 0.2 @Fau catalyst depolymerization showed obvious wrinkles and cracks on the surface of PVC particles, indicating the aging modification of the microplastic surface by free radicals.
[0066] The Co prepared in Example 1 0.2 @Fau The catalyst was used as the "catalyst" in the "catalyst depolymerization experiment on PVC microplastic particles" to depolymerize (stirring time was 12h or 48h) PVC microplastic particles. The depolymerized PVC solution was screened to separate the depolymerized PVC particles and the catalyst. The particle size distribution of the depolymerized PVC microplastic particles was tested. Figure 5 The infrared reflective glass slide loaded with the depolymerized PVC particle product was analyzed by 8700LDIR using the fully automatic "particle analysis" method in Clarity software. The results are shown in Figure 5 As shown in (a) Figure 5 "PVC-12h" and "PVC-48h" respectively represent that the Clarity software judges the PVC particle products after depolymerization for 12h and 48h as PVC microplastic particles. Figure 5 "PVC treated-12h" and "PVC treated-48h" respectively represent that the Clarity software judged the PVC particle products after depolymerization for 12h and 48h as PVC microplastic particles with some functional group peaks missing. Figure 5 "Undefined-12h" and "Undefined-48h" respectively represent that the Clarity software judges the PVC particle products after depolymerization for 12h and 48h as unrecognizable). Figure 5 As shown in (a) and (b), the PVC microplastic particles under different depolymerization conditions are widely distributed in the particle size range from 300-350nm to 20-50nm. Compared with the particle size of the PVC microplastic particles after depolymerization for 12h, the Co 0.2@Fau After the catalyst depolymerized PVC microplastic particles for 48 hours, the particle distribution in the low particle size range increased significantly, indicating that the zeolite molecular sieve catalyst loaded with single cobalt atoms can effectively degrade and transform microplastic particles.
[0067] When the catalyst is Co prepared in Example 1 0.2 @Fau catalyst, the mass loss of PVC microplastic particles in the depolymerized PVC solution obtained at different stirring times (depolymerization time) in the aforementioned "catalyst depolymerization experiment of PVC microplastic particles" is as follows Figure 6 The mass loss of PVC microplastic particles in the depolymerized PVC solution was obtained by following the above-mentioned "depolymerization experiment of PVC microplastic particles by catalyst" but without adding catalyst and stirring for 12, 24, 36 and 48 hours (different depolymerization times). Figure 6 As shown in "PVC-Control" in Figure 6 As shown in the figure, in the control group (“PVC-Control”) with no catalyst added and only PMS present, the mass loss of PVC microplastic particles was less than 5% within 48 hours. 0.2 @Fau catalyst depolymerizes PVC solution for 48 hours and the mass loss rate can reach about 17%, which shows that free radicals not only age and modify the surface of nanoparticles but also cause the breakage of chemical bonds of long-chain molecules.
[0068] The Co prepared in Example 1 0.2 @Fau catalyst depolymerized the PVC solution 4 times (single reaction 48h), and dried at 60°C for 12h after each depolymerization. At 48h after the fourth depolymerization, a mass loss rate of 17% of PVC could still be obtained.
[0069] Figure 7 The Co prepared in Example 1 0.2 @Fau Catalyst UV-vis spectra of PVC microplastic particles at different times of depolymerization according to the aforementioned "catalyst depolymerization experiment on PVC microplastic particles". It can be seen from the UV-vis spectrum that when λ<221nm, the absorbance of PVC microplastic particles depolymerized for 48 hours is less than that of PVC microplastic particles depolymerized for 12 hours. When λ>221nm, the absorbance of PVC microplastic particles depolymerized for 48 hours decreases, but is higher than that of PVC microplastic particles depolymerized for 12 hours, which shows the change of the chemical structure of PVC microplastic particles.
[0070] Figure 8 (a) is the Co prepared in Example 1 0.2 @Fau Raman test of catalyst depolymerization of PVC microplastic particles at different times, by Figure 8As shown in (a), the C-Cl bonds and CH 2 The intensity of the CH bond peaks gradually decreases, indicating the breakage of long-chain molecules and the loss of functional groups. Figure 8 (b) is the Co prepared in Example 1 0.2 @Fau catalyst depolymerization PVC microplastic particles NMR spectra at different times, using confocal Raman microscopy (ThermoScientificDXR2) to collect NMR spectra. 13 C NMR spectra were used to characterize the changes in the chemical bond functional groups of PVC microplastic particles after depolymerization for 12h or 48h. 12 C NMR spectra revealed significant changes. Figure 8 From (b), we can see that 4 to 5 ppm is the long chain molecule of PVC -(CH 2 CHCl) n -CHCl-, 2 to 3 ppm corresponds to -CHCl-CH 2 -CHCl-CH 2 , the peak intensity decreases with the extension of depolymerization time, while the typical -OH and CH 2 and CH 3 The groups also showed a significant decrease in peak intensity, indicating that the long-chain molecular content of PVC microplastic particles is decreasing, and PVC is gradually depolymerized as the depolymerization time increases. 4.2ppm corresponds to -CH=CH-CH 2 CH in Cl 2 The hydrogen on Cl, 5-6ppm is the hydrogen on the double bond, proving that PVC undergoes dechlorination reaction. 2 The peak intensities of each hydrogen on =CHOH- are gradually increasing, especially the peak intensity of the hydrogen on the carbon connected to the hydroxyl group is clearly visible. This is attributed to the poor stability of the double bonds in the molecular chain of PVC microplastic particles after dechlorination, and further redox transformation occurs, which corresponds to the chemical bond breaking results in the Raman results.
[0071] Fig. 9 (a) is the Co prepared in Example 1 0.2 @Fau laser infrared image of catalyst depolymerizing PVC microplastic particles for 12 hours, Fig. 9 (b) is the Co prepared in Example 1 0.2 @Fau laser infrared image of catalyst depolymerizing PVC microplastic particles for 48 hours, Fig. 9 (c) is Fig. 9 Laser infrared imaging of PVC microplastic particles in (a). Fig. 9 (d) is Fig. 9(b) is the laser infrared imaging image of PVC microplastic particles. The laser infrared imaging image selected several representative positions of the laser infrared imaging image of PVC fibers in the area, and normalized their infrared spectral signals. After 12 hours of depolymerization, the infrared spectral signals of 5 different positions (A1, A2, A3, A4 and A5) of the PVC microplastic particles (PVC fibers in the form of long strips) were tested and normalized. After 48 hours of depolymerization, the infrared spectral signals of 5 different positions (corresponding to the positions of 12 hours of depolymerization) B1, B2, B3, B4 and B5 of the PVC microplastic particles (PVC fibers in the form of long strips) were tested and normalized, as shown in the figure. Fig. 9 As shown in (a), Fig. 9 The "PVC" in the figure is the standard PVC signal card in the database. The characteristic peak signals at five different positions all correspond to the standard PVC signal card. This first shows that the PVC microplastic particles selected in the experiment are not contaminated. By comparing the changes in the characteristic peak signal intensity at different positions, it is found that as the particle size of infrared imaging particles decreases, CC, -CH 2 The intensity of the characteristic peak signals of -CH was significantly weakened, which indicates that the breakage of the PVC long chain is accompanied by the 2 and the gradual breaking of -CH bonds and transformation of functional groups. Fig. 9 (a) and Fig. 9 Compared with (b), as the depolymerization time increases, the intensity of the characteristic peak signal of the chemical bond of the PVC microplastic particles also decreases. For example, the infrared signal shows that the PVC microplastic particles at position B5 are almost completely decomposed into short-chain small molecules. Fig. 9 As shown in (c) and (d), the Co prepared in Example 1 0.2 @Fau After the catalyst depolymerized the PVC microplastic particles for 12 hours, the laser infrared imaging showed that the long PVC fibers were gradually decomposed and aged, and more small-sized particles appeared after 48 hours of depolymerization, indicating that the degree of degradation of the PVC fibers was deepened.
[0072] Fig.10 The Co prepared in Example 1 0.2The free radical signal spectra of different active oxygen species generated during the depolymerization of PVC by the Fau catalyst and the Fau catalyst prepared in Example 4 are used to analyze the generation of active oxygen species in different PMS activation systems by electron paramagnetic resonance (EPR) detection. 2,2,6,6-tetramethylpiperidin-1-oxyl free radical (TEMPO) and 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) are free radical scavengers that can capture short-lived free radicals and convert them into stable TEMPO / DMPO free radical addition products, thereby showing different spectral signals. The free radical and non-free radical capture experiments were detected by paramagnetic resonance spectrometer, 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) was used to quench free radicals, and 2,2,6,6-tetramethylpiperidin-1-oxyl free radical (TEMPO) was used to quench non-free radicals.
[0073] OH、SO 4 · - Test method: When testing, add 500 mg PVC and 10 mg catalyst (the catalyst is Co prepared in Example 1) into a 100 ml beaker. 0.2 @Fau catalyst or the Fau catalyst prepared in Example 4) and 100 ml of deionized water, and then immediately add 60 mg of PMS, then start timing, take 30 μL of sample after 5 minutes of reaction, and add it to 30 μL of the first mixture (the first mixture is a mixture of DMPO and water, and the DMPO concentration in the first mixture is 100 mmol·L -1 ), after mixing evenly, a certain amount of the substance to be tested is drawn with a capillary, and then placed in a quartz tube and placed in the EPR sample chamber for ·OH, ·SO 4 · - The test results are as follows Fig.10 as shown in (b).
[0074] 1 O 2 Test method: same as "·OH, ·SO 4 · - The test method is basically the same as that of the first test method, the only difference is that "30 μL of the first mixture" is replaced by "50 μL of the second mixture", the second mixture is a mixture of TEMPO and water, and the concentration of TEMPO in the second mixture is 100 mmol·L -1 , the test results are as follows Fig.10 As shown in (a).
[0075] Fig.10 (a) is 1 O 2 Free radical signal spectrum, TEMPO captures singlet oxygen ( 1 O 2) The free radical signal spectrum shows a 1:1:1 triplet peak characteristic signal, Fig.10 (b) is ·OH / SO 4 · - The electronic free radical signal spectrum shows a signal peak of 1:2:2:1 in the free radical signal spectrum of DMPO reacting with hydroxyl radicals and sulfate radicals. Fig.10 (a) and Fig.10 (b) shows that compared with the Fau catalyst prepared in Example 4, the Co0.2@Fau catalyst prepared in Example 1 1 O 2 and OH / SO 4 · - The peak values in the free radical signal spectrum increased significantly, indicating that it promoted the activation of PMS, thereby generating a large amount of 1 O 2 、SO 4 · - And ·OH, further dominated and participated in the depolymerization of PVC.
[0076] The PVC depolymerization products in the depolymerized PVC solution were qualitatively and quantitatively analyzed by GC-MS. Fig.11 The Co prepared in Example 1 0.2 @Fau catalyst depolymerization of PVC microplastic particles at different times of gas chromatography-mass spectrometry (GC-MS), the TRACE1300-ISQ7000 gas chromatography-mass spectrometry (GC-MS) was used to analyze the products after depolymerization of PVC microplastic particles. It can be seen that the gas peaks of depolymerized PVC microplastic particles after 12 hours and 48 hours have changed significantly. In the retention time range of 5 to 15 minutes, more small peaks appeared after 48 hours of depolymerization of PVC microplastic particles, which is attributed to the increase in the number of products generated as the depolymerization time increases. The products were identified according to the NIST database, among which more than 20 short-chain organic compounds were detected (Table 2 and Table 3).
[0077] Table 2 Products determined by GC / MS after 12 h of depolymerization
[0078]
[0079]
[0080] Table 3 Products determined by GC / MS after 48h of depolymerization
[0081]
[0082]
[0083] Fig.12The Co prepared in Example 1 0.2 @Analysis of products of Fau catalyst depolymerization of PVC microplastic particles at different times (based on GC / MS test results). Fig.12 As shown, the identified products (various short-chain organic compounds in Tables 2 and 3) were classified and analyzed. With the increase of depolymerization time, the products of C4-C6 and C10-C13 decreased significantly, while the proportion of C1-C3 products increased significantly.
[0084] When the catalyst is the cobalt single atom-loaded zeolite molecular sieve catalyst prepared in Example 2, the mass loss of PVC microplastic particles in the depolymerized PVC solution obtained at different stirring times (depolymerization times) in the aforementioned "depolymerization experiment of PVC microplastic particles by catalyst" is as follows: Fig.13 When the catalyst is the cobalt-loaded zeolite molecular sieve catalyst prepared in Example 3, the mass loss of PVC microplastic particles in the depolymerized PVC solution obtained at different stirring times (depolymerization times) in the aforementioned "depolymerization experiment of PVC microplastic particles by catalyst" is as follows: Fig.13 As shown in "PVC-Example 3" in the figure.
[0085] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A zeolite molecular sieve catalyst loaded with single cobalt atoms, It is characterized in that The Co content in the zeolite molecular sieve catalyst loaded with cobalt single atoms is 1-3 wt%.
2. The method for preparing the zeolite molecular sieve catalyst loaded with cobalt single atoms as claimed in claim 1, It is characterized in that The following steps are involved: 1) Dispersing a Co source uniformly in a solvent, adding an ethylene polyamine organic amine and mixing until uniform, then adding an Al source, an alkali metal source and an inorganic silicon source and mixing until uniform to obtain a mixture, reacting the mixture at 100-150° C. for 1-2 days to obtain a reactant gel, wherein, by molar mass, the ratio of Co in the Co source, Al in the Al source and alkali metal in the alkali metal source is (9-27):(90-95):(935-940); 2) washing the reactant gel to neutrality, drying, and calcining at 500-600° C. for 5-7 h to obtain a calcined sample; 3) The calcined sample is subjected to multiple ion exchanges, dried after the ion exchange, and calcined at 60-90° C. for 5-7 h to obtain a zeolite molecular sieve catalyst (octahedral zeolite molecular sieve catalyst) loaded with cobalt single atoms, wherein each ion exchange operation comprises: immersing the calcined sample in 50-80° C. NaNO 3 Place in aqueous solution for 10 to 15 hours, remove and wash until neutral.
3. The preparation method according to claim 2, It is characterized in that In the step 1), the ratio of the amount of Co in the Co source, the volume of the solvent, the volume of the ethylene polyamine organic amine and the volume of the inorganic silicon source is (51-154): (60-100): 1: (10-13), the unit of the amount of the substance is mmol, and the unit of the volume is mL.
4. The preparation method according to claim 2, It is characterized in that In the step 1), the solvent is deionized water.
5. The preparation method according to claim 2, It is characterized in that In the step 1), the ethylene polyamine organic amine is diethylene triamine.
6. The preparation method according to claim 2, It is characterized in that In the step 2), the calcination atmosphere is air.
7. The preparation method according to claim 2, It is characterized in that In step 3), the NaNO 3 The concentration of the aqueous solution is 0.8~1.1M.
8. The preparation method according to claim 2, It is characterized in that In the step 3), the ion exchange is performed 2 to 4 times.
9. The preparation method according to claim 2, It is characterized in that In step 2) and step 3), the drying temperature is 90-100° C. and the drying time is 10-12 hours.
10. Use of the zeolite molecular sieve catalyst loaded with cobalt single atoms as claimed in claim 1 in the degradation of PVC microplastics.
Citation Information
Cited By
Simple preparation method and application of metal monatomic catalyst containing carbon vacancies
CN120838452A
